Perfil sociodemográfico, comportamental e clínico¬nutricional de idosos atendidos no laboratório de nutrição do hospital universitário João de Barros Barreto (HUJBB) - SANTOS, Elis Maria da Costa (2023)
The improvement in social and health conditions led to a significant increase in life expectancy rates. This phenomenon is a challenge for health services due to the increased risk and prevalence of agerelated diseases. Because of this demographic transition, the present study aimed to characterize the sociodemographic, behavioral and clinical profile of the elderly assisted in a nutrition laboratory at a university hospital in the state of Pará. This is a crosssectional, descriptive, and quantitative study, which included 156 elderly people of both sexes assisted by the nutrition service. Data were obtained through the application of a form, and the assessment of nutritional status was performed using the Mini Nutritional Assessment and functional and cognitive capacity assessed according to the Katz index and the MiniMental State Examination, respectively. Statistical analysis was performed using the BioEstat software, version 5.0. There was a prevalence of elderly people aged 6069 years (54%), women (71%), low education (54%), income less than or equal to 1 minimum wage (47%), non drinkers (97%), nonsmokers (95%), the low practice of physical activity (76%), high functional independence (84%, without cognitive impairment (75%). The number of elderly people with more than one disease simultaneously was high (78%). Although the nutritional status was normal in most of the sample (79%), there was a prevalence of overweight according to BMI (54%). It is concluded that this study allowed draw a characteristic profile of this population and found results similar to those characteristics in the bibliography. Knowledge of such data contributes to the provision of adequate and, consequently, more effective services to the elderly public, highlighting the importance of frequent development of research in the field to favor healthy and active aging in this population.